2016
DOI: 10.5139/ijass.2016.17.4.551
|View full text |Cite
|
Sign up to set email alerts
|

Vibratory loads and response prediction for a high-speed flight vehicle during launch events

Abstract: High-speed flight vehicles (HSFVs) such as space launch vehicles and missiles undergo severe dynamic loads which are generated during the launch and in in-flight environments. A typical vehicle is composed of thin plate skin structures with high-performance electronic units sensitive to such vibratory loads. Such lightweight structures are then exposed to external dynamic loads which consist of random vibration, shock, and acoustic loads created under the operating environment. Three types of dynamic loads (ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In these standards, 5 it is advised to avoid using these levels if there is any measurement data. Kin et al 6 examined the military standard levels, compared the vibration levels with the performed measurements and showed that levels given by the military standard were exaggerated. Following these standards may lead to overdesigning of the parts due to their large conservatism of the actual response levels.…”
Section: Introductionmentioning
confidence: 99%
“…In these standards, 5 it is advised to avoid using these levels if there is any measurement data. Kin et al 6 examined the military standard levels, compared the vibration levels with the performed measurements and showed that levels given by the military standard were exaggerated. Following these standards may lead to overdesigning of the parts due to their large conservatism of the actual response levels.…”
Section: Introductionmentioning
confidence: 99%